Dispersive liquid–liquid microextraction using ammonium O,O-diethyl dithiophosphate (DDTP) as chelating agent and graphite furnace atomic absorption spectrometry for the determination of silver in biological samples - Dittert, Ingrid M.; Vitali, Luciano; Chaves, Eduardo S.; Maranhão, Tatiane A.; Borges, Daniel L. G.; Favere, Valfredo T. de; Curtius, Adilson J. (My University, 2014)
A new method for the determination of silver in biological samples is presented in this work. The method involves application of dispersive liquid–liquid microextraction (DLLME) employing ammonium O,O-diethyl dithiophosphate (DDTP) as the chelating agent for extraction and preconcentration of silver prior to quantification using graphite furnace atomic absorption spectrometry (GFAAS). Chloroform and acetone were selected as the extracting and dispersing solvent, respectively, at optimized volumes of 80 mL and 500 mL, respectively. The concentration of DDTP and the extraction time were optimized as 0.01% (m/v) and 10 min, respectively. Pyrolysis (1100 C) and atomization (1800 C) temperatures were optimized using a L'vov platform treated with 400 mg of tungsten as a permanent chemical modifier. The method was proven virtually free from interference from major constituents of biological samples. A detection limit of 2 ng g 1 was obtained with relative standard deviations better than 13% and an enhancement factor of 70 was achieved. The determined concentrations for Ag in certified reference biological samples were in good agreement with the certified values at a 95% statistical confidence limit. The reported method using DLLME and GFAAS presented good analytical performance for Ag determination when compared to other methods available in the literature.